STUDYING THE EFFECT OF FINANCIAL LITERACY, FINTECH, AND INNOVATION CAPABILITY ON MSMEs PERFORMANCE: A STUDY OF MSMEs IN INDONESIA - Pradnyani, Ni Luh Putu Sri Purnama; Setyawati, Amelia; Hadikusumo, Reina A.; Nishantha, Busige (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2025)
MSMEs are the backbone of the national economy, but many still face obstacles in financial management, access to funding, and innovation competitiveness. Therefore, understanding the factors that drive improved MSME performance is very important to support inclusive economic growth. This study aims to analyze the effect of financial literacy, utilization of financial technology (Fintech), and innovation capabilities on the performance of MSMEs in Indonesia. This study uses a quantitative approach using survey data collected from MSME actors in various regions and sectors in Indonesia. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test the direct and indirect relationships between constructs. The results of the study indicate that the three independent variables have a positive and significant effect on MSME performance. This finding implies that increasing financial literacy, adoption of financial technology, and strengthening innovation are crucial in increasing the competitiveness and sustainability of MSMEs in the digital economy era. The government and other stakeholders are advised to develop integrated training programs and policy support that encourage the integration of technology and innovation in the MSME ecosystem. Thus, MSMEs in Indonesia can be more adaptive to market dynamics and contribute more optimally to national economic development.